Metode Latihan Tabata untuk Meningkatkan Daya Tahan Anaerobik Atlet Bola Voli Pantai - Trena Rivantari; Komarudin Komarudin; Yopi Kusdinar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of the Tabata training method on increasing the anaerobic endurance of beach volleyball athletes. This study used an experimental method with a two-group pretest-posttest design. The population in this study used 12 beach volleyball athletes who were divided into two groups: the experimental group and the control group, each consisting of 6 athletes. The instrument in this study used the RAST test which was carried out before and after treatment. The experimental group was given treatment in the form of Tabata training and the control group was given conventional training. The results of the study showed an increase in anaerobic endurance in both groups, but the increase in the experimental group was more significant than the control group. Thus, the Tabata training method is more effective and is recommended as an alternative to increase the anaerobic endurance of beach volleyball athletes. Keywords: Anaerobic Endurance, Beach Volleyball, Tabata Training.